Melatonin affects the motility and adhesiveness of in vitro capacitated boar spermatozoa via a mechanism that does not depend on intracellular ROS levels. (1st June 2018) - Rocco, Martina; Betarelli, Rafael; Placci, Anna; Fernández‐Novell, Josep M.; Spinaci, Marcella; Casao, Adriana; Muiño‐Blanco, Teresa; Cebrián‐Pérez, José A.; Peña, Alejandro; Rigau, Teresa; Bonet, Sergi; Castillo‐Martín, Miriam; et al.
Summary: This work sought to address the effects of melatonin during in vitro capacitation (IVC) and progesterone‐induced acrosome exocytosis (IVAE) in boar spermatozoa. With this purpose, two different experiments were set. In the first one, IVC and IVAE were induced in the absence or presence of melatonin, which was added either at the start of IVC or upon triggering the IVAE with progesterone. Different parameters were evaluated, including intracellular levels of peroxides and superoxides, free cysteine radicals and distribution of specific lectins. While melatonin neither affected most capacitation‐associated parameters nor IVAE, it dramatically decreased sperm motility, with a maximal effect at 5 μm . This effect was accompanied by a significant increase in the percentage of agglutinated spermatozoa, which was independent from noticeable changes in the distribution of lectins. Levels of free cysteine radicals were significantly lower in melatonin treatments than in the control after 4 h of incubation in capacitating medium. The second experiment evaluated the effects of melatonin on in vitro fertilising ability of boar spermatozoa. Spermatozoa previously subjected to IVC in the presence of 1 μm melatonin and used for in vitro fertilisation exhibited less ability to bind the zona pellucida (ZP) and higher percentages of monospermy. In conclusion, melatonin affects sperm motility and the stability of nucleoprotein structure and also modulates the ability of in vitro capacitated boar spermatozoa to bind the oocyte ZP. However, such effects do not seem to be related to either its antioxidant properties or changes in the sperm glycocalix.